Requests in tourist information office service encounters: An analysis of directness and gender - Salazar, Patricia; Orts, Sara (International Journal of English Studies, 2018)
Traditionally, the speech act of requesting has been regarded as a face-threatening act (Brown & Levinson, 1987) due to the impositive nature on the addressee’s negative face. Yet, in specific service encounters, requests can no longer be seen as threatening (Antonopoulou, 2001). This is the case of tourist information offices, where mitigators may not be present due to the task-oriented nature of the exchange. This study aims to widen the scope of research on service encounters by examining 147 naturally occurring requests by native speakers of English in a tourist information office taking into account the variable of gender. Our findings suggest that females used more direct questions whereas men employed want statements to a much higher extent. These results have to be understood within the context of this specific service encounter, in which direct requests do not imply impoliteness or threats to the requestee’s negative face.